Moderasi Beragama dalam Penggunaan Media Sosial di MAS Al Hikmah Bandar Lampung - muna waroh; Sabanul Yamin; Firman Rudiansyah; Miftahur Rosyd; M. Abdullah Ramadhan (Al Mufid, 2023)
The purpose of this service activity is to equip MAS Al Hikmah students in using social media which contains religious moderation and character education and to equip MAS Al Hikmah students in implementing the stages in social media containing religious moderation and character education. This service method is carried out with lectures, discussions, and questions and answers between resource persons and MAS Al Hikmah Lampung Airport students. The stages of implementing this service, namely preparation, implementation, and evaluation. Considering that the majority of MAS Al Hikmah students are Muslim, as Muslims, of course, side by side with non-Muslims in using social media. Of course this is very necessary regarding the science of religious moderation, in order to provide understanding to students so they can sort out the information or writing that they will consume and post. The results of this service show that religious moderation is very much needed in the use of social media and recommends teaching religious moderation through instilling Pancasila values ​​in increasing moderation among religious people in Indonesia by finding a solution to preventing conflicts and divisions in social media at this time, so that it is hoped that students MAS Al Hikmah can tolerate each other among religious people, especially when on social media and become a human being who has a moderate and dignified character